Construction of Harmonization and Productivity in Teacher and Student Interactions at Madrasah Ibtidaiyah - Ichsan, Ahmad Shofiyuddin; Al Basyari, M. Mahbub; Qoyim, Muh (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2023)
This study aimed to determine the construction of harmonization and productivity in interactions between teachers and students at Madrasah Ibtidaiyah. This study method used descriptive qualitative research with the type of library research. The study results showed that teachers had to recognize students' needs and character, maintain inspiration, enthusiasm, and cheerfulness in the school environment, be patient and responsible, take advantage of things they liked in the learning process, give appreciation to children's efforts, and build good relationships with students' parents. Not only that, in the current digital era, teacher interaction needs to be understood from the Net Generation concept, namely through interaction, participation, and discourse. These three stages needed to be implemented by Madrasah Ibtidayah teachers in a balanced manner through the quality of interaction between teachers and students so that the educational civilization in Madrasah gets better to welcome a Golden Indonesia in 2045.